ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA MUSYRIF PADA PONDOK PESANTREN NAHRUL HAYAH YOGYAKARTA - Nugroho, Jalu (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
Islamic boarding schools are Islamic educational institutions that are familiar to the Muslim population in Indonesia. Islamic boarding schools are an alternative place where we can study with continuity of activities in one dormitory condition. Musyrif is a term for administrators at the Nahrul Hayah Yogyakarta Islamic Boarding School, where the musyrif's job is to guide the students. This research is to analyze the factors that influence the performance of musyrif at the Nahrul Hayah Yogyakarta Islamic Boarding School. This type of research is included in qualitative research using analytical descriptive methods, namely describing the situation of the events being studied. So the data obtained from this researcher is in the form of observations, interviews, field notes and photo shoots. From the research conducted by the author of this study, it is clear that ability, motivation, knowledge, discipline, trust, environment, workload, communication, experience and responsibility are factors in the low performance of musyrif at the Nahrul Hayah Yogyakarta Islamic Boarding School. the need to prepare, select and evaluate musyrif at the Nahrul Hayah Yogyakarta Islamic Boarding School.